The mediating role of academic self-efficacy in the relation between parent - adolescent relationship and academic performance - Fam, Jia Yuin; Yaacob, Siti Nor (Perpustakaan Sultan Abdul Samad, Universiti Putra Malaysia, 2015)
Factors influencing academic performance among adolescents are the hot topic of all time. The present study investigated the relationships between parent-adolescent relationship, academic self-efficacy and academic performance among adolescents in Malacca, Malaysia. One step ahead, the present study further examined the mediating role of academic self-efficacy in the relation between parent-adolescent relationship and academic performance. For this purpose, a total of 446 secondary school students were recruited to participate in the present study. The findings revealed significant association between academic self-efficacy and academic performance. Although Pearson correlation analysis also revealed significant association between parent adolescent relationship and academic performance, but the association was no longer existed after controlling for academic self-efficacy. In addition, Sobel test and bootstrapping also confirm indirect effect of parent-adolescent relationship on academic performance. Clearly, the relation between parent-adolescent relationship and academic performance was fully mediated by academic self-efficacy. Implications of the findings and suggestions for future research were provided.